2022
DOI: 10.3389/fgene.2022.985227
|View full text |Cite
|
Sign up to set email alerts
|

CFAP300 mutation causing primary ciliary dyskinesia in Finland

Abstract: Primary ciliary dyskinesia (PCD) is a rare genetic condition characterized by chronic respiratory tract infections and in some cases laterality defects and infertility. The symptoms of PCD are caused by malfunction of motile cilia, hair-like organelles protruding out of the cell that are responsible for removal of mucus from the airways and organizing internal organ positioning during embryonic development. PCD is caused by mutations in genes coding for structural or assembly proteins in motile cilia. Thus far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Our study has shown that HYDIN variants explain 22% of the analysed cases (4/16) in the Finnish patient cohort. Other recurrent PCD-causing variants were previously reported in CFAP300 (17%, three families) and DNAH11 (11%, two families) (Schultz, Elenius et al 2020, Schultz, Elenius et al 2022). There is still work to be done to establish a more complete gene panel for genetic diagnostics in Finland, but several Finnish population enriched variants have been identified thus far and this information can be used for improving clinical diagnostics for PCD.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Our study has shown that HYDIN variants explain 22% of the analysed cases (4/16) in the Finnish patient cohort. Other recurrent PCD-causing variants were previously reported in CFAP300 (17%, three families) and DNAH11 (11%, two families) (Schultz, Elenius et al 2020, Schultz, Elenius et al 2022). There is still work to be done to establish a more complete gene panel for genetic diagnostics in Finland, but several Finnish population enriched variants have been identified thus far and this information can be used for improving clinical diagnostics for PCD.…”
Section: Discussionmentioning
confidence: 62%
“…In Finland genetic mutations in PCD patients have previously been identified only in the DNAH11 and CFAP300 genes (Schultz, Elenius et al 2020, Schultz, Elenius et al 2022). The HYDIN variants identified in this study contribute to the understanding of the genetic background of PCD in Finland and enable development of genetics diagnostics within the Finnish population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported that genetic, immunologic, and environmental factors may increase the risk for type 1 diabetes mellitus (T1DM) [ 7 , 8 ]. The role of PCD in the development of T1DM has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%